Light‐Emitting Diodes: Record High External Quantum Efficiency of 19.2% Achieved in Light‐Emitting Diodes of Colloidal Quantum Wells Enabled by Hot‐Injection Shell Growth (Adv. Mater. 8/2020). Issue 8 (24th February 2020) - Liu, Baiquan; Altintas, Yemliha; Wang, Lin; Shendre, Sushant; Sharma, Manoj; Sun, Handong; Mutlugun, Evren; Demir, Hilmi Volkan
Abstract : In article number 1905824, Evren Mutlugun, Hilmi Volkan Demir, and co‐workers report light‐emitting diodes (LEDs) made from colloidal quantum wells (CQWs) that reach record external quantum efficiencies close to the theoretical limit (≈20%) in the case of light extraction from planar surfaces, matching the performance levels of other soft‐materials such as colloidal quantum dots (CQDs). These results usher in a new candidate for solution‐processed nanocrystal LED technology toward commercial applications in high‐quality displays and lighting.